Changes in proximal femoral mineral geometry precede the onset of radiographic hip osteoarthritis: The study of osteoporotic fractures. - Javaid, M; Lane, N; Mackey, D; Lui, L; Arden, N; Beck, T; Hochberg, M; Nevitt, M (2009)
OBJECTIVE: Radiographic hip osteoarthritis (RHOA) is associated with increased hip areal bone mineral density (aBMD). This study was undertaken to examine whether femoral geometry is associated with RHOA independent of aBMD. METHODS: Participants in the Study of Osteoporotic Fractures in whom pelvic radiographs had been obtained at visits 1 and 5 (mean 8.3 years apart) and hip dual x-ray absorptiometry (DXA) had been performed (2 years after baseline) were included. Prevalent and incident RHOA phenotypes were defined as composite (osteophytes and joint space narrowing [JSN]), atrophic (JSN without osteophytes), or osteophytic (femoral osteophytes without JSN). Analogous definitions of progression were based on minimum joint space and total osteophyte score. Hip DXA scans were assessed using the Hip Structural Analysis program to derive geometric measures, including femoral neck length, width, and centroid position. Relative risks and 95% confidence intervals for prevalent, incident, and progressive RHOA per SD increase in geometric measure were estimated in a hip-based analysis using multinomial logistic regression with adjustment for age, body mass index, knee height, and total hip aBMD. RESULTS: In 5,245 women (mean age 72.6 years), a wider femoral neck with a more medial centroid position was associated with prevalent and incident osteophytic and composite RHOA phenotypes (P < 0.05). Increased neck width and centroid position were associated with osteophyte progression (both P < 0.05). No significant geometric associations with atrophic RHOA were found. CONCLUSION: Differences in proximal femoral bone geometry and spatial distribution of bone mass occur early in hip OA and predict prevalent, incident, and progressive osteophytic and composite phenotypes, but not the atrophic phenotype. These bone differences may reflect responses to loading occurring early in the natural history of RHOA.